PlantFAdb: a resource for exploring hundreds of plant fatty acid structures synthesized by thousands of plants and their phylogenetic relationships. (9th November 2018) - Ohlrogge, John; Thrower, Nick; Mhaske, Vandana; Stymne, Sten; Baxter, Melissa; Yang, Weili; Liu, Jinjie; Shaw, Kathleen; Shorrosh, Basil; Zhang, Meng; Wilkerson, Curtis; Matthäus, Bertrand
Summary: Over 450 structurally distinct fatty acids are synthesized by plants. We have developed PlantFAdb.org, an internet‐based database that allows users to search and display fatty acid composition data for over 9000 plants. PlantFAdb includes more than 17 000 data tables from >3000 publications and hundreds of unpublished analyses. This unique feature allows users to easily explore chemotaxonomic relationships between fatty acid structures and plant species by displaying these relationships on dynamic phylogenetic trees. Users can navigate between order, family, genus and species by clicking on nodes in the tree. The weight percentage of a selected fatty acid is indicated on phylogenetic trees and clicking in the graph leads to underlying data tables and publications. The display of chemotaxonomy allows users to quickly explore the diversity of plant species that produce each fatty acid and that can provide insights into the evolution of biosynthetic pathways. Fatty acid compositions and other parameters from each plant species have also been compiled from multiple publications on a single page in graphical form. Links provide simple and intuitive navigation between fatty acid structures, plant species, data tables and the publications that underlie the datasets. In addition to providing an introduction to this resource, this report illustrates examples of insights that can be derived from PlantFAdb. Based on the number of plant families and orders that have not yet been surveyed we estimate that a large number of novel fatty acid structures are still to be discovered in plants. Significance Statement: Within the plant kingdom several hundred different fatty acid structures are synthesized and many of these have important applications in industry, nutrition, pharmacy and cosmetics. The PlantFAdb website and database compiles data from over 3000 publications on more than 9000 plants and allows users to explore connections between fatty acid structures and plant species by displaying these relationships on dynamic phylogenetic trees.